Review of Prospective Trials for Degenerative Cervical Myelopathy. Issue 10 (21st December 2022) - Satin, Alexander M.; Rush, Augustus J.; Derman, Peter B.
Abstract : Degenerative cervical myelopathy (DCM) is the leading cause of spinal cord dysfunction in adults. DCM refers to a collection of degenerative conditions that cause the narrowing of the cervical canal resulting in neurological dysfunction. A lack of high-quality studies and a recent increase in public health awareness has led to numerous prospective studies evaluating DCM. Studies evaluating the efficacy of surgical intervention for DCM can be characterized by the presence (comparative) or absence (noncomparative) of a nonoperative control group. Noncomparative studies predominate due to concerns regarding treatment equipoise. Comparative studies have been limited by methodological issues and have not produced consistent findings. More recent noncomparative studies have established the safety and efficacy of surgical intervention for DCM, including mild myelopathy. The optimal surgical intervention for DCM remains controversial. A recent randomized clinical trial comparing dorsal and ventral techniques found similar improvements in patient-reported physical function at early follow-up. Recent prospective studies have enriched our understanding of DCM and helped guide current treatment recommendations.